Design and testing of circular metamaterial-based salinity sensors - Yona Purnama Rezki; Romi Fadli Syahputra; Delovita Ginting (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2023)
The salinity sensor is a salt level detection tool designed based on the electrical properties of water. The salinity sensor consists of two electrodes that are dipped in water where the sensor is given a potential difference so that electrons flow in the sensor-building circuit. The electrode is connected to a variable resistor which forms a voltage divider circuit connection. This research aims to design a metamaterial (MTM) sensor to detect salt levels in the 100 – 900 MHz range and investigate the performance of MTM sensors for detecting salt levels. The working MTM sensor design has been successfully designed and tested, where the MTM sensor is also able to differentiate frequency values from samples with different salt levels.